2021
DOI: 10.1001/jamaoncol.2020.6343
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Integrated Palliative and Oncology Care for Patients With Acute Myeloid Leukemia

Abstract: IMPORTANCEPatients with acute myeloid leukemia (AML) receiving intensive chemotherapy experience substantial decline in their quality of life (QOL) and mood during their hospitalization for induction chemotherapy and often receive aggressive care at the end of life (EOL). However, the role of specialty palliative care for improving the QOL and care for this population is currently unknown.OBJECTIVE To assess the effect of integrated palliative and oncology care (IPC) on patient-reported and EOL outcomes in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
113
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 111 publications
(130 citation statements)
references
References 74 publications
2
113
0
Order By: Relevance
“…15,16 Data from randomised controlled trials suggest the integration of a palliative care approach with some treatments with curative intent, such as HSCT 17 and induction chemo therapy in patients with acute myeloid leukaemia. 18 This is in line with the WHO definition of palliative care: to address patients with lifethreatening disease, not only those with incurable disease. 19 With a median age at diagnosis of about 70 years, most haematological malignancies have an ageassociated increase in incidence and mortality.…”
Section: Challengessupporting
confidence: 68%
“…15,16 Data from randomised controlled trials suggest the integration of a palliative care approach with some treatments with curative intent, such as HSCT 17 and induction chemo therapy in patients with acute myeloid leukaemia. 18 This is in line with the WHO definition of palliative care: to address patients with lifethreatening disease, not only those with incurable disease. 19 With a median age at diagnosis of about 70 years, most haematological malignancies have an ageassociated increase in incidence and mortality.…”
Section: Challengessupporting
confidence: 68%
“…Indeed, one recent randomized control trial among adults with acute myeloid leukemia demonstrated that integrating palliative care was associated not only with decreased receipt of chemotherapy at the EOL but also with substantial improvements in patient-reported quality of life and decreases in psychological distress. 21 Though not randomized, numerous pediatric studies have also conclusively demonstrated that palliative care can positively affect how they live, right until the very end. 22 Children with hematologic cancer deserve to benefit from palliative care as much as anyone else.…”
mentioning
confidence: 99%
“…This was a secondary analysis of data from 160 hospitalized patients with AML who were enrolled in a multisite, nonblinded, randomized palliative care intervention trial at Massachusetts General Hospital (Boston, Massachusetts), Duke University Medical Center (Durham, North Carolina), the Hospital of the University of Pennsylvania (Philadelphia, Pennsylvania), and Ohio State University (Columbus, Ohio) between January 2017 and July 2019 14 . The study was approved by the Institutional Review Boards at all participating sites.…”
Section: Methodsmentioning
confidence: 99%